Geography of political awareness of urban residents in Babylon Governorate For the year 2022: A study in social geography - Jawamir, Safaa; Sajt, Ali (Al-Adab Journal, 2024)
This study aimed to identify the level of political awareness in the urban population of Babil Governorate. The measure of political awareness was used, which consists of several axes (cognitive, emotional, media, participation in elections and the political process). Expected value analysis (intersection of questions) was used to show the relationship between the answers of the respondents, and the values of the moral score were Zero, which leads us to reject the null theory and accept the alternative hypothesis, which states that there is a relationship between the indicators and the validity of the answers. For this purpose, the descriptive analytical approach was used, and a questionnaire tool consisting of (40) indicators was applied to the population of the study area, and the number of questionnaires reached (1100) for the year (2022). The study reached the following results:- The study reached the average level of political awareness and on various demographic variables. The value of political awareness at the governorate level reached (594). In addition, there is spatial variation in the level of awareness through the percentages of answers to the indicators by the respondents, as they were distributed among three variables (Agree, No opinion, disagree. The highest level of political awareness was recorded in Markaz Al-Mahawil district with a value of (685) and the lowest level of political awareness in Al-Kifl district with a value of (531). The study reached a coefficient of variation value of (12.18), and this explains the extent of the variation in levels of political awareness.The one-way analysis of variance resulted in rejecting the null hypothesis when using a significant level (0.05%) and accepting the alternative hypothesis, which indicates a difference between the averages of the answers according to the districts through the value of the arithmetic mean scores, as the values ranged between (0.828 and 14.824), as well as the moral value Which equals zero.The researcher recommended the following:- Spreading political awareness among the population of the study area about the importance of participating in the political process and participating in the elections, which contributes to correcting voluntary behavior and providing the opportunity for women to participate.- Relying on reliable and official sources to obtain local and regional political news for its role in building an image of the political reality and developing individual knowledge.- Educating the study community about political culture to provide a democratic climate and respect for personal freedom and intellectual pluralism to mature a sense of citizenship and social and political responsibility.